BUILDING INFORMATION MODELLING AND RISK IN INDUSTRIALISED BUILDING SYSTEM PROJECTS: A SCIENTOMETRIC REVIEW - Saipudin, Noorul Amilin; Nurfadzillah Ishak (Journal of Surveying, Construction and Property, 2025)
The scholarly exploration of Building Information Modelling (BIM), risk management, and Industrialised Building System (IBS) research has expanded rapidly, reflecting the construction industry’s increasing reliance on digital and prefabricated technologies. Despite this growth, there remains a fragmented understanding of how research in these areas has developed over time, including dominant themes, influential contributors, and methodological trends. This study addresses this gap through a scientometric review of 1,153 publications retrieved from the Scopus database between 2010 and 2025. Using VOSviewer and Scopus analytical tools, publication trends, document types, co-authorship networks, and keyword co-occurrence were systematically examined to provide a structured overview of the field. The analysis reveals a steady increase in scholarly output, particularly after 2015, indicating rising global interest in technology-driven risk management and prefabricated construction methods. Journal articles constitute the majority of the literature, followed by conference papers and reviews, reflecting the evolution of research dissemination. Geographical and citation analyses show that countries such as China, Malaysia, and the United Kingdom dominate the field, while highly cited authors provide conceptual and methodological foundations for emerging studies. Keyword analysis highlights recurring themes of safety, process optimization, digital innovation, and project management. Despite the rapid expansion of literature, persistent gaps remain, including limited empirical validation, uneven adoption across industry contexts, and the lack of standardized methodologies. By mapping these patterns and gaps, this scientometric review offers a critical lens on the evolution of BIM, Risk, and IBS research, providing scholars and practitioners with actionable insights on knowledge trends, collaborative networks, and potential directions for future investigation. Overall, this work supports informed decision-making and fosters the development of rigorous, context-sensitive research agendas in construction studies.